Outcomes of dorsal nasal augmentation using costochondral graft - Amna Kifayatullah; Mamoon Rashid; Saad Ur Rehman; Ibrahim Khan (Journal of the Pakistan Medical Association, 2024)
Objective: To assess functional and aesthetic outcomes in patients having undergone dorsal nasal augmentation with costochondral graft in a tertiary care setting. Method: The single-centre, retrospective, observational study was conducted at Shifa International Hospital, Islamabad, Pakistan, and comprised data of patients who underwent dorsal nasal augmentation using costochondral graft between January 1, 2018, and December 31, 2022. Aesthetic outcomes in terms of patient satisfaction were assessed using Facial Appearance, Health-related Quality of Life and Adverse Effects scores. Data was analysed using SPSS 26. Results: Of the 46 patients, 28(61%) were males and 18(39%) were females. The overall mean age was 28.39+9.13 years. Dorsal nasal deficiency occurred secondary to congenital causes in 12(26.1%) patients, trauma 19(41.3%) and prior surgery 15(32.6%). Postoperative complication rate was 7(15%); 3(6.5%) had recipient site infection and 2(4.3%) had rib graft resorption. Besides, 1(2.2%) patient reported pain 2 months postoperatively and 1(2.2%) had hypertrophic scarring. Patient satisfaction with the outcome was noted in all the 10 parameters analysed. Most commonly reported problem was that the nose was ‘looking thick/swollen’ by 12(26.1%) patients, but the issue resolved during 1-year follow-up. Conclusion: Costochondral graft was found to be an ideal material for dorsal nasal augmentation, with high patient satisfaction rate. Key Words: Costal cartilage, Patient satisfaction, Rhinoplasty.